وسائل الدفع الالكتروني بين توقعات العملاء والقيمة المدركة للخدمة دراسة ميدانية على عملاء المصارف التجارية (Comprehensive Journal of Science, 2025)
The study aimed to measure customer attitudes towards the use of electronic payment methods by comparing their perceptions based on their experiences with their expectations of the benefits they hoped to gain. To achieve these objectives, a descriptive approach was used. To collect data, the target population was defined as customers of commercial banks that provide electronic payment services. Given the dispersion of the population and the difficulty of accurately identifying and accessing it, an electronic questionnaire was designed to provide equal opportunities to access the specific sample (384)  individuals. After analysing the data obtained, the study reached some conclusions, the most important of which is that electronic payment methods in their current form do not meet customer needs due to the reluctance of many business owners to use electronic payment methods. Most of the study's respondents agreed that the issuance of legislation and laws requiring all commercial and service activities to use electronic payment methods and their monitoring by regulatory authorities would increase their reliability, along with the development of the infrastructure supporting electronic payment methods.